English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-10-30 13:05:19 · 7 answers · asked by Anonymous in Science & Mathematics Mathematics

7 answers

7x - 2(x+2) -3 = 4x + 5
---> 5x - 7 = 4x + 5
----> x = 12

2006-10-30 13:07:57 · answer #1 · answered by James Chan 4 · 0 0

x=12

2006-10-30 21:26:36 · answer #2 · answered by J 6 · 0 0

x=12

2006-10-30 21:15:38 · answer #3 · answered by jeannemarie11 2 · 0 0

x=12

2006-10-30 21:14:47 · answer #4 · answered by benniria 2 · 0 0

7x - 2x -4 - 3 = 4x +5
5x-7=4x+5
-4x......-4x
x-7 =5
+7....+7
x = 12
check
7(12) -2(12+2)-3 =4(12)+5
84 -28 -3 = 48 +5
84-31 = 53 yes

2006-10-30 21:09:06 · answer #5 · answered by dla68 4 · 0 0

We have,
7x - 2(x+2) -3 = 4x +5
or 7x - 2x -4 -3 = 4x + 5
or 5x - 7 = 4x + 5
or 5x - 4x = 7 + 5
or x = 12
Hence the solutioni x =12

2006-10-30 21:09:34 · answer #6 · answered by anjali 2 · 0 0

7x - 2(x+2) -3 = 4x + 5
7x -2x - 4 - 3 = 4x +5
5x - 7 = 4x +5
5x - 4x = 5+7
x = 12

2006-10-30 21:09:57 · answer #7 · answered by redstorm 3 · 0 0

fedest.com, questions and answers